Adopción de las normas Internacionales de información financiera por primera vez en el Sindicato de Choferes profesionales de Cotopaxi en la ciudad de Latacunga. - Pastrana Corozo, Brithany Estefania (2023)
This project was developed through information obtained from the Sindicato de Choferes Profesionales de Cotopaxi, as a recommendation of an external Audit performed to the financial statements to show the real situation of the entity in the period of adoption year 2022, in order to adopt the International Financial Reporting Standards for the first time in the Sindicato de Choferes Profesionales de Cotopaxi (Driving School) in the city of Latacunga. The methodology used was quantitative to obtain data from the entity, carrying out a descriptive and non-experimental research, which allowed visualizing and identifying existing and relevant events of the daily activities that take place in the SME. The field research created an environment of direct contact with reality and allowed the establishment of objectives for the application of IFRS. The documentary-bibliographic research, in order to obtain information from different authors and a broad approach to IFRS. The deductive and analytical-synthetic methods to obtain and interpret the results of the interviews conducted. Finally, the respective accounting adjustments were made, in the assets component there was a decrease of -18.89% as an effect of the IFRS transition, due to the revaluation and derecognition of the entity's fixed assets. As for liabilities, there was an increase of 73.75% due to the deferred tax generated by the revaluation. Finally, in equity, a decrease of -20.41% due to the revaluation and the increase in expenses, which is reflected in the profit under IFRS year 2022 with a value of $106,497.92 as opposed to the profit under NEC year 2021 which is $ 222,757.83 representing 52.19%, which affects the decrease in equity due to the profits generated.